SOCIALIZATION OF THE ACCURACY REGARDING THE CALCULATION OF RECAPITULATION FOR INPATIENTS BASED ON AGE, DISEASE AND GENDER AT CHARIS MEDIKA HOSPITAL - Riza Suci Ernaman Putri; Widya Putri; Melfina Triani (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2024)
A hospital is one of the subsystems of health services that organizes two types of services for the community, namely health services and administrative services. Health services include medical services, medical rehabilitation and care services. Every health service or hospital should be proud if every patient who visits continues to increase, the increase in patients can be seen from the changes in the existing graph of the number of patient visits. The number of patient visits that continues to increase greatly affects the smooth running of each health service, because patients who often visit have high trust in the health service they visit. The number of visits for inpatients for postpartum care based on age, disease, and gender is 115 visits, the number of visits for care patients based on age, disease, and gender is 37 visits. It can be concluded that medical records officers should write down inpatient data completely and clearly in the register book, good communication between medical records officers and doctors treating patients should be good so that the diagnosis written by the doctor in the patient's medical record is easy to read.